2018
DOI: 10.1145/3196885
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Distance Estimation in HMD-Based Virtual Environments with Different HMD-Based Conditions

Abstract: Underestimation of egocentric distances in immersive virtual environments using various head-mounted displays (HMDs) has been a puzzling topic of research interest for several years. As more commodity-level systems become available to developers, it is important to test the variation of underestimation in each system since reasons for underestimation remain elusive. In this article, we examine several different systems in two experiments and comparatively evaluate how much users underestimate distances in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 37 publications
6
66
1
1
Order By: Relevance
“…This hypothesis is consistent with the notion that path integration error accrues with travel distance, and thus larger travel distances would produce larger errors. It is also consistent with research showing that distance in virtual reality is under-perceived, and that such perceptual errors are proportional to the actual distance (see [12,33] for reviews), even in modern displays [7,20].…”
Section: Meterssupporting
confidence: 88%
“…This hypothesis is consistent with the notion that path integration error accrues with travel distance, and thus larger travel distances would produce larger errors. It is also consistent with research showing that distance in virtual reality is under-perceived, and that such perceptual errors are proportional to the actual distance (see [12,33] for reviews), even in modern displays [7,20].…”
Section: Meterssupporting
confidence: 88%
“…The weight of the HMD itself might also contribute to the phenomenon [44]. Recent studies have shown that modern HMDs significantly reduce distance underestimation in VR, even if some differences remain about their distance compression depending on the experimental conditions [9,26].…”
Section: Related Workmentioning
confidence: 99%
“…The question of distance underestimation within HMDs has been examined extensively with adults, using the traditionally heavier and limited-field-of-view HMDs, as well as more recent comparisons to commodity-level HMDs. Recent consensus with commodity-level HMDs points to less underestimation of distance compared to what was traditionally found in early studies (Young et al, 2014;Creem-Regehr et al, 2015b;Kelly et al, 2017;Buck et al, 2018). Given that recent work still finds some distance compression in IVEs in the HTC Vive with adults (Kelly et al, 2017), perhaps children perceived even less compression than teens or adults, which would provide an alternative explanation for their more conservative affordance judgments (i.e., if children perceive the width of the gap to be farther, then they would choose a smaller interval as crossable).…”
Section: Body-scaled Affordances For Gap Crossing In the Ivementioning
confidence: 95%